DETERMINANTS OF DEMOCRATIC LEADERSHIP, COMPETENCE AND MOTIVATION TOWARDS THE ACHIEVEMENT OF THE VISION OF XYZ UNIVERSITY - Mangkupradja, Didi Rochyadi; Pramukty, Rachmat; Junianti, Emmy; Karsono, Bambang; Widyastuti, Tri (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to analyze the factors that influence the achievement of the vision of XYZ University. The factors studied are democratic leadership, competence, and motivation. This research is important to understand how these factors contribute to the success of educational institutions in achieving the set vision. The research method used was survey research using a questionnaire as a data collection instrument. Respondents in this study were staff and lecturers at XYZ University. The collected data were analyzed using regression techniques to identify the relationship between the variables studied. The results of this study indicate that democratic leadership, competence, and motivation have a positive and significant influence on the attainment of the vision of XYZ University. Democratic leadership that involves the active participation of all members of the university, strong competence of staff and lecturers, as well as high motivation to achieve a shared vision, are important factors in achieving the university's strategic goals. The implications of this research are the importance of building democratic leadership, increasing individual competency through training and development, and fostering high motivation among staff and lecturers. In the university context, these factors can become the basis for achieving the set vision, enhancing the university's reputation, and creating a quality academic environment.